Mixed Stacked Charge‐Transfer π‐Organic Materials Based on Anthracenyl Boronic Acid. Issue 47 (21st December 2017) - Petroselli, Manuel; Mosca, Sara; Martí‐Rujas, Javier; Comelli, Daniela; Cametti, Massimo
Abstract : Anthracenyl boronic acid derivatives are used for the first time as hydrogen‐bond and π‐donors to obtain a series of novel 1:1 mixed stacked π‐organic materials with interesting structural, UV/Vis reflectance and emission properties by reaction with quinones in both solution and the solid. The underlying principles, which have led to hetero‐assembly, could be applied to construct a potentially large variety of mixed stacked π‐organic solid‐state materials for technological applications. Abstract : The hetero‐assembly principles to synthesize novel charge‐transfer materials by reacting HB‐ and π‐donor anthracenyl boronic acids with quinones, both in solution and the solid state, are described.